Frailty status predicts futility of cardiopulmonary resuscitation in older adults. (5th June 2020) - Ibitoye, Sarah E; Rawlinson, Sadie; Cavanagh, Andrew; Phillips, Victoria; Shipway, David J H
Abstract: Aim: To determine if frailty is associated with poor outcome following in-hospital cardiac arrest; to find if there is a "frailty threshold" beyond which cardiopulmonary resuscitation (CPR) becomes futile. Methods: Retrospective review of patients aged over 60 years who received CPR between May 2017 and December 2018, in a tertiary referral hospital, which does not provide primary coronary revascularisation. Clinical Frailty Scale (CFS) and Charlson Comorbidity Index were retrospectively assigned. Results: Data for 90 patients were analysed, the median age was 77 (IQR 70-83); 71% were male; 44% were frail (CFS > 4). Frailty was predictive of in-hospital mortality independent of age, comorbidity and cardiac arrest rhythm (OR 2.789 95% CI 1.145–6.795). No frail patients (CFS > 4) survived to hospital discharge, regardless of cardiac arrest rhythm, whilst 13 (26%) of the non-frail (CFS ≤ 4) patients survived to hospital discharge. Of the 13 survivors (Age 72; range 61–86), 12 were alive at 1 year and had a good neurological outcome, the outcome for the remaining patient was unknown. Conclusion: Frail patients are unlikely to survive to hospital discharge following in-hospital cardiac arrest, these results may facilitate clinical decision making regarding whether CPR may be considered futile. The Clinical Frailty Scale is a simple bedside assessment that can provide invaluable information when considering treatment escalation plans, as it becomes more widespread, larger scale observations using prospective assessments of frailty may become feasible.